Exoskeleton-Robot Assisted Therapy in Stroke Patients: A Lesion Mapping Study - Cerasa, Antonio; Pignolo, Loris; Gramigna, Vera; Serra, Sebastiano; Olivadese, Giuseppe; Rocca, Federico; Perrotta, Paolo; Dolce, Giuliano; Quattrone, Aldo; Tonin, Paolo (Frontiers in Neuroinformatics, 2018)
Background: Technology-supported rehabilitation is emerging as a solution to support therapists in providing a high-intensity, repetitive, and task-specific treatment, aimed at improving stroke recovery. End-effector robotic devices are known to positively affect the recovery of arm functions, however there is a lack of evidence regarding exoskeletons. This paper evaluates the impact of cerebral lesion load on the response to a validated robotic-assisted rehabilitation protocol. Methods: 14 hemiparetic patients were assessed in a within-subject design (age 66.9 ± 11.3 years; 10 men and 4 women). Patients, in post-acute phase, underwent 7 weeks of bilateral arm training assisted by an exoskeleton robot combined with a basal conventional treatment (consisting of simple physical activity together with occupational therapy). Clinical and neuroimaging evaluations were performed immediately before and after rehabilitation treatments. Fugl-Meyer and Motricity Index were selected to measure primary outcomes, i.e., motor function and strength. Functional independence measure and Barthel Index were selected to measure secondary outcomes, i.e., daily living activities. Voxel-based lesion symptom mapping (VLSM) was used to determine the degree of cerebral lesions associated with motor recovery. Results: Robot-assisted rehabilitation was effective in improving upper limb motor function recovery, considering both primary and secondary outcomes. VLSM detected that lesion load in the superior region of the corona radiata, internal capsule and putamen were significantly associated with recovery of the upper trunk as defined by the Fugl-Meyer scores (p-level < 0.01). Conclusions. The probability of functional recovery from stroke by means of exoskeleton robotic rehabilitation relies on the integrity of specific subcortical regions involved in the primary motor pathway. This is consistent with previous evidence obtained with conventional neurorehabilitation approaches.